Pembangunan sistem perakaunan untuk syarikat kecil dan sederhana kes siswaniaga - Mohamed, Amdan; Md Saleh, Md Suhaimi (Universiti Utara Malaysia, 2007)
This is the product development type of research project where, at the end it will produce simple accounting software. The objective of this project is to help the small and medium size in managing the accounting information so that they can manage their company well.This project is planned to develop accounting software with two basic module namely General Ledgers and Sales Modul.It can also produce most basic accounting and finance report such as Income Statement, Trial Balance, Ledger, Balance Sheet, Income Statement.. where it complies with generally acceptable accounting principles.